L-Glutamate production by lysozyme-sensitive Corynebacterium glutamicum ltsA mutant strains - Hirasawa, Takashi (BioMed Central, 2001)
BACKGROUND: A non-pathogenic species of coryneform bacteria, Corynebacterium glutamicum, was originally isolated as an L-glutamate producing bacterium and is now used for fermentative production of various amino acids. A mutation in the C. glutamicum ltsA gene caused susceptibility to lysozyme, temperature-sensitive growth, and L-glutamate production. RESULTS: The characteristics of eight lysozyme-sensitive mutants which had been isolated after N-methyl-N'-nitro-N-nitrosoguanidine mutagenesis were examined. Complementation analysis with the cloned wild-type ltsA gene and DNA sequencing of the ItsA region revealed that four mutants had a mutation in the ltsA gene. Among them, two mutants showed temperature-sensitive growth and overproduced L-glutamate at higher temperatures, as well as the previously reported ltsA mutant. Other two showed temperature-resistant growth: one missense mutant produced L-glutamate to some extent but the other nonsense mutant did not. These two mutants remained temperature-resistant in spite of introduction of ltsA::kan mutation that causes temperature-sensitive growth in the wild-type background. CONCLUSIONS: These results indicate that a defect caused by the ltsA mutations is responsible for temperature-sensitive growth and L-glutamate overproduction by C. glutamicum. The two temperature-resistant mutants seem to carry suppressor mutations that rendered cells temperature-resistance and abolished L-glutamate overproduction.